COMPUTATIONAL PREDICTION OF A PROPELLER PERFORMANCE IN OPEN WATER CONDITION - Ahmad Fitriadhy; N. Amira Adam; CJ. Quah (Universitas Mercu Buana, 2020)
In presence of hydrodynamics phenomena occur surrounding propeller evidently affects on accuracy’s prediction of thrust, torque and its efficiency. To achieve the objective, a Computational Fluid Dynamics (CFD) simulations approach is then proposed to obtain a reliable prediction of the thrust (KT), torque (KQ) and efficiency (η) coefficients in open water condition. The effect of various blade numbers associated with constant propeller revolution (RPM=1320) and pitch ratio (P/D=1.0); are performed within the range of advance ratio from 0.1J1.0. The results revealed that the increase of blade number from Z=3 to 5 was proportional with the increase of thrust (KT) and torque (KQ) coefficients; meanwhile, it was reduced the maximum efficiency (η) that possibly lead to downgrade the propeller performance. It should be noted here, the propeller with three blade numbers (Z=3) provide the highest efficiency (η) up to 78.8% at J=0.9. These CFD simulation results are very useful as a preliminary study of propeller characteristics.